Corporate PR in a post-Citizens United world. Issue 2 (29th April 2014) - Myers, Cayce; Lariscy, Ruthann
Abstract : Purpose: – The purpose of this paper is to provide an overview of the historical evolution of campaign finance laws and suggest the legal implications for public relations practitioners after the US Supreme Court's decision in Citizens United v. FEC . Design/methodology/approach: – The approach of this paper examines appellate case law and federal statutes to provide a legal analysis of the history of campaign finance laws and potential impact on public relations practitioners. Findings: – This research provides an overview of the evolution of campaign finance case law and federal statues in the USA and provides analysis of how the 2010 Citizens United case and a recent 2012 case, American Trade Partnership, are altering both the political and corporate landscapes. By allowing far greater contribution rights to corporations than any time since 1907, Citizens United is changing the role corporations may directly play in elections at all levels. Implications for how these changes may affect corporate public relations practitioners both professionally and ethically are discussed. Practical implications: – In a post- Citizens United era, corporate PR may now legally be engaged with many forms of highly political communications. Corporate PR may have a more political tone and ethical dilemmas may face practitioners who may be legally asked to perform communications tactics that are at odds with their political values. Originality/value: – Despite the academic analysis of Citizens United no study has evaluated the effect Citizens United and campaign finance laws on public relations practice.